An educational alternative for improving working conditions in small and medium enterprises - Eliana Castro S; Elisabeth Herreño T (Universidad de Antioquia, 2011)
Managing health and safety at work involves considering two internal processes common to all organizations: knowledge and human talent management. These two processes are affected by globalizing phenomena that have an effect at the economic, environmental, and occupational levels. This is especially true for countries like Colombia. Objective: to provide an educational alternative that contributes to knowledge management in SME's in order to improve the working conditions and to support their innovation processes. Methodology: an exploratory and descriptive study. We start by analyzing the concepts related to the improvement of working conditions and experiences from previous projects involving the university-industry relationship. This is done from the systemic viewpoint that characterizes the ergonomics and interdisciplinary perspectives of the professional practice of industrial design. Result: the proposal was approved by regional institutions wishing to conduct a pilot study, and is based on principles establishing health promotion at the workplace. It also includes a methodology for affecting the technological core of companies and contributes to the empowerment of the personnel involved. Conclusion:it is mandatory that organizations express their support and commitment through a policy that facilitates the active participation of employees in these processes.